A pilot study examining the effects of priming headache illness schema on attentional engagement towards pain relief medication, in those with high and low medication treatment beliefs. Issue 7 (9th August 2017) - Ahluwalia, Monisha; Hughes, Alicia M; McCracken, Lance M; Chilcot, Joseph
Abstract: Few studies have assessed the underlying theoretical components of the Common Sense Model. Past studies have found, through implicit priming, that coping strategies are embedded within illness schema. Our aim was to evaluate the effect priming 'headache' illness schema upon attentional engagement to pain relief medication and to examine the interaction with illness treatment beliefs. Attentional engagement to the pain relief medication ('Paracetamol') was assessed using a 2 (primed vs. control) × 2 (strong belief in medication efficacy vs. weak belief in medication efficacy) design. During a grammatical decision task (identifying verbs/non-verbs), participants were randomised to receive a headache prime or a control. Response latency to the target word, 'Paracetamol' was the dependent variable. 'Paracetamol' treatment beliefs were determined using the brief illness perception questionnaire. Sixty-three participants completed the experiment. There was a significant interaction between illness-primed vs. control and high vs. low treatment efficacy of Paracetamol ( p < .001), suggesting an attentional disengagement effect to the coping strategy in illness-primed participants whom held stronger treatment beliefs regarding the efficacy of Paracetamol. In summary, implicit illness schema activation may simultaneously activate embedded coping strategies, which appears to be moderated by specific illness beliefs.